2000
DOI: 10.1080/10413200008404213
|View full text |Cite
|
Sign up to set email alerts
|

The profile of mood states and athletic performance: Two meta-analyses

Abstract: The present study was a meta-analysis of 29 published studies that used the Profile of Mood States (POMS) to investigate relationships between mood and athletic achievement or between mood and performance outcome. Results showed that effect sizes (ESs) for level of achievement were minimal (n = 15, Weighted Mean ES = 0.10, SD = 0.07), a finding consistent with a previous meta-analysis by Rowley, Landers, Kyllo, and Etnier (1995).Larger effects were found for performance outcome (n = 17, Weighted Mean ES = 0.31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
255
4
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 308 publications
(276 citation statements)
references
References 43 publications
13
255
4
4
Order By: Relevance
“…Disrupted sleep negatively affects mood generalises to athletic populations [16], and mood is associated with subsequent athletic performance, it can be seen that disrupted sleep could negatively affect sporting performance via changes is mood states [17].…”
Section: Resultsmentioning
confidence: 99%
“…Disrupted sleep negatively affects mood generalises to athletic populations [16], and mood is associated with subsequent athletic performance, it can be seen that disrupted sleep could negatively affect sporting performance via changes is mood states [17].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, some findings remain supportive of the notion that athletic achievement can be differentiated from mood scores (e.g., Morgan, Brown, Raglin, O'Connor, & Ellickson, 1987;Trafton, Meyers, & Skelly, 1998) precipitating two recent meta-analyses by Beedie, Terry, and Lane (2000) that summarised the findings of 13 published studies investigating whether mood responses can differentiate athletes of varying degrees of achievement and 16 published studies investigating whether mood responses can differentiate performance outcome among athletes of similar ability. Beedie et al concluded that mood responses have significant utility in the prediction of performance outcome but not in the prediction of level of achievement.…”
Section: Measurement Issuesmentioning
confidence: 97%
“…The meta-analysis of Beedie et al (2000) showed that, when studies investigating level of achievement and studies using inappropriate methods were excluded, the mean effect of mood on performance was small-to-moderate (Mean ES = .31). Effects were moderate for vigour, confusion, and depression, small for anger and tension, and very small for fatigue.…”
Section: Measurement Issuesmentioning
confidence: 99%
“…Meta-analysis has shown (Beedie, Terry, & Lane, 2000;LeUnes & Burger, 2000) that the characteristics of mood states can predict the performance of athletes in different sports. The question is whether this feature can be identified in elite sailors from their performances in different races.…”
Section: Introductionmentioning
confidence: 99%